The territorial logic of an export-led growth strategy: Israel's regime change after the Second Intifada - Arie Krampf (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
In recent decades, neo-mercantilism has become ubiquitous among small and large states. The conventional explanation for the appeal of an export-led growth regime has focused on the material interests of domestic growth coalitions. This article offers an alternative explanation for transition to export-led growth strategies, based on the geopolitical and territorial interests of states. It posits that states embrace a mercantilist export-led growth model because it aligns with their geopolitical objectives. The article demonstrates the geopolitical hypothesis based on the transition of Israel from a consumption-led to an export-led growth strategy after the end of the peace process and the outbreak of the Second Intifada in 2000.
Keywords: O53; O43; N15; E12; 330; Export-led growth strategy; neo-mercantilism; growth coalition; territorial logic of capitalism